2020
DOI: 10.1109/access.2020.3019658
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Encrypted Cryptomining Malware Connections With Machine and Deep Learning

Abstract: resources to the crypto-currency mining pools they benefit from. This research work focuses on offering a solution for detecting such abusive cryptomining activity, just by means of passive network monitoring. To this end, we identify a new set of highly relevant network flow features to be used jointly with a rich set of machine and deep-learning models for real-time cryptomining flow detection. We deployed a complex and realistic cryptomining scenario for training and testing machine and deep learning models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Each security enabler generates data with standard protocols such as Net-Flow v9 [28] or IPFIX, but also provide additional contextual data with 12 statistical information of TCP flows [29]: Round Trip Time (RTT), TCP protocol flags (such as SYN or ACK) , windows scale or Maximum Segment Size (MSS) per flow. The aggregation of this supplementary data source has already demonstrated a clear increment in the performance of the ML algorithms in this specific crypto-mining problem [30]. Accordingly, it is expected that additional network attacks to the 5G Core using encrypted traffic will be detected by the Security Analytic Engine with new ML models based on the same aggregated data provided by the Security Data Collector.…”
Section: Applying Data Aggregation To 5g Securitymentioning
confidence: 93%
“…Each security enabler generates data with standard protocols such as Net-Flow v9 [28] or IPFIX, but also provide additional contextual data with 12 statistical information of TCP flows [29]: Round Trip Time (RTT), TCP protocol flags (such as SYN or ACK) , windows scale or Maximum Segment Size (MSS) per flow. The aggregation of this supplementary data source has already demonstrated a clear increment in the performance of the ML algorithms in this specific crypto-mining problem [30]. Accordingly, it is expected that additional network attacks to the 5G Core using encrypted traffic will be detected by the Security Analytic Engine with new ML models based on the same aggregated data provided by the Security Data Collector.…”
Section: Applying Data Aggregation To 5g Securitymentioning
confidence: 93%
“…We observed in preliminary experiments that very deep networks with a large number of hidden layers or units did not generate significant improvements in performance and on the contrary, they enlarged convergence times and produced non-negligible oscillations in the convergence during the training process. This effect could be explained by the fact that the cryptomining classification problem does not need very complex models to obtain a decent accuracy 13 . Therefore, we selected a moderate number of hidden layers (between 3 and 5) for generator and discriminator networks.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Cryptomining attacks concern the network traffic generated by cybercriminals that create tailored and illegal processes for catching computational resources from users’ devices without their consent to use them in the benefit of the criminal for mining cryptocurrencies. It has been shown that these malicious connections can be detected in real-time with decent accuracy even at the very beginning of the connection’s lifetime by using an ML classifier 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach is nevertheless susceptible to evasion using JavaScript obfuscation and bears a substantial operational burden associated with HTTPS proxies. Several papers [90][91][92][93] rely on computing features upon packet flows and training binary classification machine learning models. They achieve high detection accuracy at the expenses of computation and deployment overhead.…”
Section: Network-based Detectionmentioning
confidence: 99%